2008
DOI: 10.1002/cphc.200800099
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Au Nanoparticles as Substrates for Surface‐Enhanced Vibrational Spectroscopy: Optimization and Electrochemical Stability

Abstract: Three-dimensional nanostructured metallic substrates for enhanced vibrational spectroscopy are fabricated by self-assembly. Nanostructures consisting of one to 20 depositions of 13 nm-diameter Au nanoparticles (NPs) on Au films are prepared and characterized by means of AFM and UV/Vis reflection-absorption spectroscopy. Surface-enhanced polarization modulation infrared reflection-absorption spectroscopy (PM-IRRAS) is observed from Au NPs modified by the probe molecule 4-hydroxythiophenol. The limitation of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 57 publications
(83 reference statements)
4
49
1
Order By: Relevance
“…So far, many nanostructured metal materials have been tested as SERS substrates. [1][2][3][4][5][6][7][8][9][10][11][12] It has been shown that the SERS enhancement factor depends on the size, morphology, and assembly of the nanoparticles. The ability to prepare a nanostructured array with controlled particle size and interparticle distance would allow one to control the resonance frequency of the localized surface plasmon and to opportunely match it with the incident laser wavelength, resulting in larger SERS enhancements.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many nanostructured metal materials have been tested as SERS substrates. [1][2][3][4][5][6][7][8][9][10][11][12] It has been shown that the SERS enhancement factor depends on the size, morphology, and assembly of the nanoparticles. The ability to prepare a nanostructured array with controlled particle size and interparticle distance would allow one to control the resonance frequency of the localized surface plasmon and to opportunely match it with the incident laser wavelength, resulting in larger SERS enhancements.…”
Section: Introductionmentioning
confidence: 99%
“…Different surface sensitive characterization techniques were used to evaluate the functionalized surfaces including PM-IRRAS which was used to monitor the adsorption and organization of the monolayer, similarly to recent work in the literature. [28][29][30] The motivation is to reduce the electrochemical signal from gold, avoiding fouling surfaces and thus lead to functionalized surfaces amenable to adsorption of biomolecules for efficient SPR based biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering cross section and the electric field around the particle can reach very high values in the spectral vicinity of the surface plasmon resonances. Hence, metal nanoparticles find additional applications in the enhancement of field-sensitive optical processes, in, for example, fluorescence enhancement (Käll et al 2005;Härtling et al 2007) and surface-enhanced Raman spectroscopy (Otto et al 1992;Freeman et al 1995;Grabar et al 1995;Kneipp et al 1997;Lu et al 2005aLu et al ,b, 2006Qin et al 2006;Fan & Brolo 2008;Ko et al 2008;Lu & Eychmüller 2008), as well as in environmental refractive index sensing (Raschke et al 2003;Härtling & Eng 2005).…”
Section: Introductionmentioning
confidence: 99%